2013
DOI: 10.5455/2319-2003.ijbcp20131019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of knowledge, attitude and behavior about rational use of medicines in second year medical students

Abstract: Background: To assess the knowledge about various issues concerned with rational use of medicines in second year medical students Methods: This was a survey-based, cross-sectional study in which a self developed, pre-tested, semi-structured questionnaire was used. Respondents were 153 students of second year MBBS (beginning of third semester). They were explained about nature and purpose of study and necessary consent obtained. Questions were framed to obtain information about various issues concerned with use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…Majority of the 68% of students were are aware that wide variation in costs of different brands of same drug is available in the market. Our study observations are similar in accordance with previous study done by Sontakke SD et al 12 It is very crucial that these concepts remain in students minds, it is possible only when all these issues are repeatedly reinforced upon them and they are made to realize the 5 Doctors can completely depend on information about drugs given by pharma industries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Majority of the 68% of students were are aware that wide variation in costs of different brands of same drug is available in the market. Our study observations are similar in accordance with previous study done by Sontakke SD et al 12 It is very crucial that these concepts remain in students minds, it is possible only when all these issues are repeatedly reinforced upon them and they are made to realize the 5 Doctors can completely depend on information about drugs given by pharma industries.…”
Section: Discussionsupporting
confidence: 92%
“…The study questionnaire consisted of a pre-validated, semi-structured, open-ended and closed-ended items. The questionnaire was obtained from the similar previous study done by Sontakke SD et al 12 Slight modifications were done in our study as per the subject experts opinion. Questionnaire was designed to obtain information about various issues concerned with rational use of medicines.…”
Section: Methodsmentioning
confidence: 99%
“…Ironically only 6% among them look fee the generic name of the drug. These findings are similar to the previous study conducted by smita.et al (7)(8) This is not an encouraging finding and needs to be corrected because using or prescribing medicines by generic names is an important measure in the rational use of drugs. A bunch of previous studies show that high incidence of drug prescribing errors and irrational usage of drugs is mainly due to inadequate pharmacology teaching (9)(10)(11)(12).…”
Section: Discussion:-supporting
confidence: 86%
“…Some studies have reported improvement in the quality of health care following use of NLEM and standard treatment guidelines. [10][11][12] Hence, it is essential to adopt measures that will encourage their use. Various studies have revealed that prescribing medicines by brand name has become a routine practice.…”
Section: Discussionmentioning
confidence: 99%